Distribution of Impurities Concentration in Nucleate Boiling - G.R Jahanfarnia (مجله علوم و فنون هسته‌ای, 2008)
The development of the mathematical model of mass transfer and diffusion process can determine the behavior of dissolved impurities in the flow boiling within viscous sublayer. Application of a new model to calculate the distribution of dissolved impuritiesconcentration within viscous sublayer and estimation of its thickness based on heat conduction layer and evaporation layer (macro-microlayer model) is the major goal of this study.